Design of Biosolvents Through Hydroxyl Functionalization of Compounds with High Dielectric Constant - Ou, Guangnan; He, Biyan; Yuan, Youzhu; 袁友珠 (2012)
NSFC [51004053, 20873108, 20923004]; Science Foundation of Jimei University; NSF of Fujian Province [2009J01033, E0720002]; National Basic Research Program of China [2011CBA00508] We proposed basic principles for biosolvent design on the viewpoint of ionization. Two classes of biosolvents, based on cyclic carbonate moiety and amide moiety, were designed through hydroxyl functionalization of highly dielectric compound. The newly designed compounds, glycerol carbonate (GC) and N-hydroxymethyl formamide (HOF), were synthesized for the development of soluble enzymatic systems and characterized by C-13 NMR and H-1 NMR. All the characterization data were consistent with the expected structures. Using conductance measurements, the pK(a) values of trichloroacetic acid in GC and HOF were determined as 0.80 and 0.85 at 25.0 degrees C, which was very close to that in water (pK(a)=0.70), suggesting that the ionizing and dissociating abilities of GC and HOF are similar to those of water. The effects of various reaction parameters on activity and stability of Candida antarctica lipase B and lipase from Pseudomonas cepacia were investigated using the transesterification of ethyl butyrate with n-butanol as a model reaction. The activities of lipases in GC and HOF were comparable to those in water, indicating that the newly designed compounds were biocompactible. Biosolvent design is a promising and versatile method for developing new biosolvents.